1999
DOI: 10.1128/mcb.19.2.1159
|View full text |Cite
|
Sign up to set email alerts
|

The trithorax Group Gene moira Encodes a Brahma-Associated Putative Chromatin-Remodeling Factor in Drosophila melanogaster

Abstract: The genes of the trithorax group (trxG) in Drosophila melanogaster are required to maintain the pattern of homeotic gene expression that is established early in embryogenesis by the transient expression of the segmentation genes. The precise role of each of the diverse trxG members and the functional relationships among them are not well understood. Here, we report on the isolation of the trxG gene moira (mor) and its molecular characterization. mor encodes a fruit fly homolog of the human and yeast chromatin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 53 publications
3
76
0
1
Order By: Relevance
“…In addition, BRG1 interacts directly with the SANT domain of SRG3. Similarly, it was shown that MOIRA, a Drosophila homologue of SRG3, interacts with BRM through the SANT domain (23). It was recently reported that BAF155 interacts with BAF57 through the leucine-zipper motif (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BRG1 interacts directly with the SANT domain of SRG3. Similarly, it was shown that MOIRA, a Drosophila homologue of SRG3, interacts with BRM through the SANT domain (23). It was recently reported that BAF155 interacts with BAF57 through the leucine-zipper motif (24).…”
Section: Discussionmentioning
confidence: 99%
“…The moira gene encodes an RNA polymerase II transcription factor that is essential for the transcriptional regulation and activity of multiple homeotic and segmentation genes, including antennapedia (40). moira is ubiquitously expressed in early development and is highly concentrated in the CNS at later stages of embryonic development (41). Embryos injected with moira dsRNA exhibited abnormal commissures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that the brahma and SuUR genes have a common origin but different functions. In any case, these observations provide additional arguments in favor of the idea that functional division into PcG repressors and trxG activators may be oversimplified (9,28). DISCUSSION The main result of this study demonstrates that SuUR is a DNA-binding protein that interacts in a specific way with BRs, sequences that separate forum domains.…”
Section: Binding Of Suur To Twomentioning
confidence: 66%
“…SuUR possesses ATPase/helicase domains found in the SNF2 family of trxG proteins in which it catalyzes ATP-dependent alterations in nucleosomal organization (28). Thus, SuUR could be considered a putative chromatin-remodeling factor, but the nature of its effect is not clear.…”
Section: Suur Protein Has Several Domains That Are Homologous To the mentioning
confidence: 99%